The Doha Agenda and Development: A View from the Uruguay Round - J. Michael Finger (Asian Development Bank (ADB), 2002)
"The Doha Agenda continues the Uruguay Round's expansion of trade negotiations into behind-the-border policies, regulations, and institutions. This distracts attention from the part of the Agenda most directly linked to poverty reduction and economic development: removal of distortions to agricultural trade and of import restrictions on industrial goods - by developing as well as developed countries. Behind-the-border areas are important for development but Uruguay Round experience indicates that trade negotiations provide here a troubled approach to development. On these, development institutions should lead. They are more comfortable with the necessary technicalities of project design and cost-benefit analysis. Development institutions' legalities are country-specific and project-specific, more suited to the one-off problems and trialerror rhythm of what is needed than is WTO's generic approach to legal obligation. If there is momentum behind the development dimensions of the new areas, then the trade dimensions can be managed; but one cannot push the string."
hdl:11540/1970
Keywords: 330; Außenwirtschaftspolitik; Handelsliberalisierung; Handelsabkommen; WTO-Recht; Nord-Süd-Beziehungen; Entwicklungsländer; Industrieländer